The Influence of Fundamental Factors on Stock Prices of the LQ-45 Index During 2020–2024 - Eryasi Daryati; Zuliyana, Ida; Yeni R, Misra (International Journal of Economics, Business and Innovation Research, 2026)
This study investigates the effect of Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), Earnings Per Share (EPS), and Price to Earnings Ratio (PER) on stock prices of companies included in the LQ-45 Index listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The study adopts a quantitative approach by analyzing 45 companies included in the LQ-45 Index, with a sample of 12 firms observed over five years, resulting in 60 observations. The results indicate that ROA and DER do not have a significant effect on stock prices, whereas CR, EPS, and PER have a significant positive effect. Simultaneously, all independent variables significantly influence the stock prices of LQ-45 companies listed on the IDX. The coefficient of determination yields a value of 74.2%, indicating that the independent variables account for 74.2% of the variation in stock prices, while the remaining 25.8% is attributed to other factors not examined in this study. These findings contribute to the literature on the Indonesian capital market and provide insights for investors and policymakers regarding the role of fundamental factors in shaping stock prices amid dynamic economic conditions.